Intelligent Head-bot, towards the Development of an AI Based Cognitive Platform - Baki, Ramisha Fariha; Akhtaruzzaman, M; Refat, Tahsin Ahmed; Rahman, Mouneeta; Razzak, Md Abdur; Majumder, Md Mahfuzul Karim; Islam, Md Adnanul; Ferdaus, Md Meftahul; Rahman, Muhammad Towfiqur; Naveed, Quadri Noorulhasan (MIST International Journal of Science and Technology, 2023)
A cognitive humanoid head is an AI enabled head-bot platform that resembles human's cognitive abilities, such as perception, thinking, learning, and decisionmaking. The platform is able to interact with human through natural language processing and recognize individuals, thus allowing seamless communication between two parties. No such cognitive platform has been introduced in Bangladesh, thus creating an open field to contribute to the field of Machine Intelligence. This study aims to develop an AI based humanoid head (head-bot) capable of imitating a range of expressions, recognizing individuals, and interacts with visitors through general conversation. The head-bot skeleton is developed using a number of hexagonal blocks of PVC sheet to mimic a humanhead- like structure where LCD, camera, microphones, and speaker are mounted. Two separate Machine Learning models are designed for face detection and recognitions, and voice enabled chat-bot implementation. The head-bot platform incorporates 2-DoF neck movements for various head gestures and face tracking. The Artificial Neural Network models are tested with accuracy of , and , for face detection and recognitions, and speech recognitions and response generation, respectively. According to the overall results and system performances, it seems that the proposed system has a number of good potentials for real life applications such as entertainment, guidance, conversations, interactive receptionists, personal companion, medical assistance, and so on. MIJST, Vol. 11, December 2023 : 01-14 DOI: https://doi.org/10.47981/j.mijst.11(02)2023.440(01-14)